Exploring the Challenges: Teacher Reluctance in Implementing Comprehensive Sexuality Education in South Africa's Foundation Phase - Venketsamy, Roy (Islamic Early Childhood Education Study Program, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga Yogyakarta, 2023)
Purpose – This study explored why South African Foundation Phase teachers are reluctant and anxious to teach Comprehensive Sexuality Education (CSE) content to young learners. The unit of analysis was Foundation Phase teachers in public schools. Design/methods/approach – Adopting a qualitative, interpretive approach, the study conducted semi-structured interviews with six teachers from primary schools in Gauteng Province. The study used thematic analysis to understand teachers' perceptions and attitudes toward CSE. The data was analysed using Creswell’s six steps of data analysis. Findings – Findings reveal a varied understanding of CSE among teachers, with some viewing it narrowly as sex education and others recognising its broader scope, including emotional development and safety. Primary reasons for reluctance include perceived age inappropriateness, discomfort with content, and cultural and religious constraints. The lack of adequate training and resources further exacerbates this reluctance. Research implications/limitations – This study on South African teachers' reluctance to teach Comprehensive Sexuality Education (CSE) in the Foundation Phase has critical implications for educational policy and practice, emphasizing the need for culturally sensitive curriculum development, comprehensive teacher training, and supportive educational environments. However, its limitations include a reliance on teacher perceptions, a small sample size from a single district, and the absence of quantitative data, which may affect the generalizability of its findings. Future research should expand geographically, employ diverse methodologies, and examine the effects of curriculum and training reforms on CSE's effectiveness in varied South African educational contexts. Practical implications – The study underscores the importance of developing a culturally sensitive, comprehensive CSE curriculum and professional development programs for South African teachers. It highlights the need for clear educational guidelines and resources to assist teachers in effectively delivering CSE content to young learners. Originality/value – This research provides a novel perspective by focusing on the reluctance of Foundation Phase teachers in South Africa to teach CSE, a relatively unexplored area in educational research. It offers valuable insights into the intersection of cultural, religious, and pedagogical factors affecting CSE delivery, contributing significantly to the global discourse on sexuality education in early childhood. Paper type Research paper